Co-creating tools to monitor first graders’ progress in reading: a balancing act between perceived usefulness, flexibility, and workload - Francotte, Eve; Colognesi, Stéphane; Coertjens, Liesje (Frontiers in Education, 2023)
Educational inequalities, i.e., achievement gaps between pupils from disadvantaged backgrounds and their peers from advantaged backgrounds, are present in many OCDE countries. This is particularly problematic in reading, which is a predictor of future academic and social success. To reduce this reading achievement gap, recent meta-analyses point towards progress monitoring: regularly measuring pupils’ mastery level and differentiating instruction accordingly. However, the research recommendations only slowly make their way to teaching habits, particularly because teachers may consider progress monitoring difficult and cumbersome to implement. To avoid such difficulties, partnerships between teachers and researchers have been recommended. These allow to take teachers’ complex realities into account and, consequently, design tools that are meaningful and feasible for practitioners. Using an iterative and participatory process inspired by practice-embedded research, the present research set out to (1) co-construct tools to monitor first-graders’ progress in reading, and, (2) examine how these tools met teachers’ needs. Five teachers in the French-speaking part of Belgium co-constructed four tools during four focus groups. The transcribed discussions were analyzed using an interactional framework containing three areas of knowledge: shared, accepted, and disputed. Results indicated three shared needs: perceived usefulness, flexibility of the tools, and a desire to limit the workload. In addition, teachers accepted that, between them, needs varied regarding the goal for progress monitoring and the format of the evaluation. They had lengthy discussions on balancing workload and perceived utility, leading them to conclude that there were two groups of teachers. The first group questioned the added value of the progress monitoring tools in relation to their habitual practice. The second group on the other hand described the added value for the teacher, certainly when aiming to grasp the level and difficulties of struggling pupils. This second group had less years of teaching experience and described their classroom practice as less organized compared to the teachers from the first group. Theoretical and practical implications of these findings are discussed.